Henoch-Schonlein Purpura with hematochezia in an adult patient - Manappallil, Robin George; Kumar, Pradeep; Anand, Thushara (Asian Journal of Medical Sciences, 2020)
Henoch-Schönlein purpura (HSP) is a self-limiting vasculitic disease, commonly seen in children. It is characterized by palpable purpura, arthritis, hematuria and abdominal pain. Hematochezia is an uncommon symptom. The patient being reported is an adult male who presented with vomiting, abdominal pain and hematochezia, followed by appearance of palpable purpura and arthritis. He was diagnosed to have HSP. Hematochezia as one of the initial presentations of HSP in adults is an uncommon scenario.